Investigating the impact of undergraduate laboratory courses, research experiences, and CUREs courses on lecture-based course material - Dirks, Kaitlyn, author (Colorado State University. Libraries, 2024)
Undergraduate STEM degrees are composed of lecture and laboratory classes. Additionally, undergraduate research experiences and core-based undergraduate research experience (CURE) are becoming more encouraged throughout a bachelor's degree. However, what is the impact of these courses and experiences on undergraduate education? This study aims to understand the benefit or lack thereof, of laboratory courses, CUREs courses, and undergraduate research experience, on that of lecture courses within STEM degrees. The results were collected by a survey and analyzed for statistical significance using the chi-squared test. Results found that both laboratory courses and undergraduate research experiences had an impact on the lecture courses. This correlation could occur from the re-iteration of the lecture course material within the lab course setting. Further the autonomy in a research experience challenges students to engage in critical thinking, application and analysis of the lecture course material. The results pertaining to the CUREs courses are currently incomplete. There were significantly few respondents who had engaged in a CUREs lab. This could have resulted from the lack of knowledge or awareness of the course. With the continuation of lab courses and a required entry level course focused on entering STEM students into undergraduate research experiences, STEM students' academic output could continue to rise. With a better spread of the CUREs course, the data could be recollected and reassessed.
Keywords: laboratory; CUREs; STEM; lecture; undergraduate